Long-term outcomes following percutaneous coronary intervention to an unprotected left main coronary artery in cardiogenic shock - Yeoh, J.; Andrianopoulos, N.; Reid, Christopher; Yudi, M.B.; Hamilton, G.; Freeman, M.; Noaman, S.; Oqueli, E.; Picardo, S.; Brennan, A.; Chan, W.; Stub, D.; et al. (ELSEVIER IRELAND LTD, 2020)
© 2020